Development of a questionnaire for patient perception to functional appliances - Anosh A. Haik; Yassir A. Yassir (BMC, 2024)
Abstract Objective To developed and evaluate the validity, reliability, and Arabic translation of a questionnaire for preadolescent perception to removable functional appliances. Subjects and methods A new questionnaire was drafted based on previously used questionnaires. Twelve orthodontic experts were selected within content and face validity panel and twenty preadolescents wearing functional appliances were participated in the face validation of the questionnaire. Two rounds of content validity were performed with the same experts. The final form of the validated questionnaire was translated from English to Arabic language. The content validity index (CVI) was used for content validity and the Cronbach's alpha test was used to assess the internal consistency reliability of the questionnaire. Results During the first round of content validity, 50 items were relevant to the underlying construct (Item-CVI ≥ 0.78), while four items were considered not valid (Item-CVI < 0.78) and the average scale-CVI was 0.93. In terms of face validation by experts, the percentage of agreement was adequate (96.4%). The questionnaire was modified by removing the non-valid items, adding/modifying items, and merging some categories. For second round of content validity, all items were found to be valid (I-CVI ≥ 0.78) and the overall questionnaire had adequate content validity (Scale-CVI/Ave = 0.94). The translated valid questionnaire also achieved a perfect agreement (100%) for face validity by patients. The internal consistency was appropriate (≥ 0.7). Conclusions A new valid, reliable, and translated questionnaire (English and Arabic versions) that cover the majority of aspects of patients' perception during treatment with removable functional appliances has been developed.